2005
DOI: 10.1002/14651858.cd002859.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of recurrent miscarriage for women with antiphospholipid antibody or lupus anticoagulant

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
266
1
30

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(305 citation statements)
references
References 95 publications
8
266
1
30
Order By: Relevance
“…A HBPM apresenta diversas vantagens em relação à HNF: melhor efeito antitrombótico, menor incidência de sangramento, meia-vida mais longa e melhor biodisponibilidade 1 . Contudo, seu uso prolongado tem sido associado a efeitos colaterais maternos, incluindo a trombocitopenia, hemorragia e osteoporose 1,6 . Embora a hemorragia seja possível complicação da terapia anticoagulante, o uso da HBPM durante a gravidez está associado a redução na incidência de eventos hemorrágicos maternos, e não se associa a sangramentos fetais 26 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A HBPM apresenta diversas vantagens em relação à HNF: melhor efeito antitrombótico, menor incidência de sangramento, meia-vida mais longa e melhor biodisponibilidade 1 . Contudo, seu uso prolongado tem sido associado a efeitos colaterais maternos, incluindo a trombocitopenia, hemorragia e osteoporose 1,6 . Embora a hemorragia seja possível complicação da terapia anticoagulante, o uso da HBPM durante a gravidez está associado a redução na incidência de eventos hemorrágicos maternos, e não se associa a sangramentos fetais 26 .…”
Section: Discussionunclassified
“…Pressupõe-se que os agentes antiplaquetários, particularmente, a aspirina em baixas doses, podem impedir ou postergar o desenvolvimento da pré-eclâmpsia 6 , pois essa condição está associada à produção insuficiente de prostaciclinas e produção excessiva de tromboxano, vasoconstrictor que estimula a agregação plaquetária. Descreve-se redução do risco de 17% no desenvolvimento de pré-eclampsia com o uso de agentes antiplaquetários 3 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Literature includes many articles with mixed results concerning the effect of this adjuvant. One of the first Cochrane reviews about aspirin administration found that when combined with unfractionated heparin it may prevent recurrent miscarriage (RM) in women with anti-phospholipid syndrome [22]. On the contrary, in a more recent meta-analysis of 4 trials, authors showed that LBRs did not improve and early miscarriage rates did not decline by the addition of heparin to low-dose aspirin in women with congenital thrombophilia [23].…”
Section: Low-dose Aspirinmentioning
confidence: 99%
“…Although bleeding can be a complication of anticoagulant therapy, the use of LMWH during pregnancy has been associated with a reduced incidence of bleeding events and an absence of maternal foetal bleeding. However, clinical and experimental studies have not demonstrated ample evidence of its safety and effects on the development of the embryo-foetus [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%